Research of Dynamic Simulation of Gear Transmission System based on Virtual Prototype Technology - Zhang Zheng; Feng Guangbin; Sun Huagang (Jixie chuandong)
A complex gear transmission system is one of the core components of a tracked vehicle. In order to study the dynamic characteristics of the gear transmission system under different operating conditions,considers the working characteristics of the torque converter and the time-varying contact force of the meshing gear pair,by using the software platforms Creo and RecurDyn,a virtual prototype simulation model of a complex transmission system is established. The model is simulated under the condition of 1-gear hydraulic pressure. The variation rules of speed and torque during starting process are analyzed. The steady-state value of speed is validated by the test values. At the same time,the time-frequency curve of contact force between gears is extracted and analyzed. The simulation process and the results provide the model and technical support for the research of the condition monitoring and fault diagnosis of the gear transmission system.